2020
DOI: 10.1186/s12886-020-01396-y
|View full text |Cite
|
Sign up to set email alerts
|

Defective angles of localized retinal nerve fiber layer reflect the severity of visual field defect- a cross-sectional analysis

Abstract: Background: In order to detect glaucomatous optic nerve damages early on and evaluate the severity of glaucoma, a previously developed analytic method based on photographic retinal nerve fiber layer (RNFL) angle defect was proposed. However, the correlation between these defective angles and the severity of visual field defect has not been verified. This study aimed to confirm the correlation described above. Methods: We reviewed a total of 227 glaucomatous eyes (38 enrolled, 189 excluded) during an interval o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

1
2
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 22 publications
1
2
0
Order By: Relevance
“…In our study we found that, GCC and RNFL were thinner in the glaucomatous eyes compared to the control subjects. This agrees with what has already been demonstrated that RNFL thickness reduction occurs in glaucoma especially measuring the angular width of localized RNFL defect is also a viable method for determining the severity of visual field defect (6,7) .…”
Section: Discussionsupporting
confidence: 91%
“…In our study we found that, GCC and RNFL were thinner in the glaucomatous eyes compared to the control subjects. This agrees with what has already been demonstrated that RNFL thickness reduction occurs in glaucoma especially measuring the angular width of localized RNFL defect is also a viable method for determining the severity of visual field defect (6,7) .…”
Section: Discussionsupporting
confidence: 91%
“…Remarkably, RNFL remained significant after controlling for disease stage. This may reflect the widening and deepening of localized RNFL defects with disease progression 85–87. Further research on the relationship between wedge defects and disease severity may provide insight into glaucoma pathophysiology.…”
Section: Discussionmentioning
confidence: 99%
“…Third, red-free fundus photographs in highly-pigmented Asian eyes clearly show the borders of localized RNFL defects, such as in our study 16 . Many studies in Asian eyes have therefore employed the measurement of RNFL defect width to assess glaucoma progression 17 21 . In addition, due to the resolution, OCT may be less sensitive than red-free fundus photographs in detecting subtle changes, especially in myopic eyes 19 , 22 28 .…”
Section: Discussionmentioning
confidence: 99%